Bulk growth of organic non-linear optical (NLO) L-arginine 4-nitrophenolate 4-nitrophenol dihydrate (LAPP) single crystals by Sankaranarayanan–Ramasamy (SR) method. (10th November 2017) - Sivasubramani, V.; Anis, Mohd; Hussaini, S. S.; Muley, G. G.; Senthil Pandian, M.; Ramasamy, P.
Abstract: Organic non-linear optical single crystals of L-arginine 4-nitrophenolate 4-nitrophenol dihydrate (LAPP) are grown by Sankaranarayanan–Ramasamy (SR) method and slow evaporation solution technique (SEST) with the sizes of about 45 mm length, 15 mm diameter and 6 × 5 × 5 mm 3, respectively. The grown crystals were characterised by single crystal X-ray diffraction to determine the crystallographic unit cell parameter values. The etch pit density of SEST and SR method grown LAPP crystals have been calculated using chemical etching analysis. The mechanical and optical properties of the SEST and SR method grown LAPP crystals are studied using Vickers microhardness and UV–vis NIR measurement, respectively. Laser damage threshold analysis has been made on cut and polished SEST and SR method grown LAPP crystal of 5 mm thickness. Photoconductivity study of LAPP crystal grown by SEST and SR method reveals positive photoconductivity nature. The thermal properties of the grown crystal were carried out by thermogravimetric and differential thermal analysis. The second-harmonic generation efficiency of LAPP crystal was determined using powder Kurtz–Perry technique and it was found to be 2.3 times that of standard potassium dihydrogen phosphate material.